Knowledge, Prevalence, Patterns, and Factors Associated with Substance Abuse among Police Officers in Enugu State, Nigeria - Uzoma Chidi Okereke; Emmanuel N. Aguwa; Stella Ngozi Okereke; Chioma NP Mbachu; Nnenna Chiloli; Nnaemeka Emmanuel Akubue; Chinekwu S. Anyaoku; Okoli Adaora Ukamaka; Igwe Onyedikachi Michael; Gibson Ifechukwude Chiejine (Journal of Public Health, Policy, and Society, 2026)
Substance abuse among law enforcement personnel poses risks to individual health, public safety, and organizational integrity. Evidence on the burden and determinants of substance abuse among Nigerian police officers is limited. This study assessed knowledge, prevalence, patterns, and factors associated with substance abuse among police officers in Enugu State, Nigeria. A descriptive cross-sectional study was conducted among 390 police officers selected through multistage sampling from police formations in Enugu State. Data were collected using a structured, self-administered questionnaire on socio-demographic characteristics, knowledge of substance abuse, substance use practices, and reasons for use. Data were analysed with SPSS version 25 using descriptive statistics. The mean age of respondents was 34.7 ± 8.7 years; 52.1% were male, 46.9% were married, and 46.4% were inspectors. Almost half (50.8%) resided in barracks. Most had secondary education (47.9%), and 83.3% earned ≤100,000 naira monthly. Awareness of commonly abused substances was high: cigarettes (94.9%), alcohol (94.6%), tramadol (70.3%), cough syrup (77.7%), cocaine (59.7%), and cannabis (54.9%). The overall knowledge score was 51.9%, indicating fair knowledge. The lifetime prevalence of substance abuse was 37.7%. Among users, the most commonly abused substances were cigarettes (98.5%), alcohol (97.7%), cocaine (59.7%), and tramadol (33.8%), while cough syrup (17.9%) was least used. The mean age of initiation was 19.6 ± 3.7 years, and 70.1% commenced use by 18 years. Some respondents (30.5%) used drugs other than those prescribed medically; 28.2% reported combining multiple non-prescribed drugs, 57.2% experienced withdrawal symptoms, and 40.5% knew someone with a drug problem. Major reasons for substance abuse included fun (82.6%), peer/social pressure (70.5%), increased energy (71.3%), and alertness (54.8%). Overwork (24.9%) and rebelliousness (6.9%) were less frequently cited. Substance abuse is a notable problem among police officers in Enugu State, with early initiation, fair but incomplete knowledge, and substantial use of cigarettes, alcohol, and other psychoactive substances. These findings underscore the need for comprehensive, context-specific interventions within the Nigeria Police Force, including structured health education, mental health and substance use services, and organizational measures to address occupational stress and promote healthy coping.